Estimating the Number of Teachers of Students With Visual Impairments in the United States. (September 2022) - Savaiano, Mackenzie E.; Shanahan Bazis, Pamela; Hebert, Michael; Rodgers, Derek B.; Bosilevac, Madison; Leutzinger, Bridget; Thompson, Madison
Introduction and Methods: We do not have an accurate count of the number of teachers of students with visual impairments working in the field, and it is a difficult number to estimate. As part of a national survey, states were contacted to estimate how many teachers of students with visual impairments are working in the United States and compared to the estimate developed by the National Plan for Training Personnel to Serve Children with Blindness and Low Vision (NPTP) in 2000. Results and Discussion: The estimate calculated from this process is very similar to the estimate from NPTP (2000), indicating that there are roughly the same number of teachers of students with visual impairments in the field now as there were 20 years ago.